Analysis of Chemical Ingredients in Jamu Pegal Linu Released in Siwa, Pitumpanua District, Wajo Regency - Maryam, St; Rahmawati, Rahmawati; Febiyanti, Azalia Zalzabila (Pharmaceutical Reports, 2025)
Jamu is an indigenous Indonesian traditional herbal medicine commonly prepared in the form of brews, powders, liquids, pills, or capsules. However, some manufacturers irresponsibly add pharmaceutical chemicals (Bahan Kimia Obat, BKO) to enhance the therapeutic effects of these products. One of the most frequently detected adulterants in jamu pegal linu—a herbal remedy used to relieve muscle and joint pain—is diclofenac sodium, a nonsteroidal anti-inflammatory drug (NSAID). This study aimed to identify and quantify the presence of diclofenac sodium in jamu pegal linu samples circulating in Siwa, Pitumpanua Sub-district, Wajo District, Indonesia. Six samples were analyzed using thin-layer chromatography (TLC) and UV-Visible spectrophotometry. The qualitative TLC analysis utilized silica gel GF254 as the stationary phase and an ethyl acetate–n-hexane (7:3) mixture as the mobile phase. All samples exhibited Rf values of 0.8, corresponding to the diclofenac sodium standard, confirming the presence of this compound. Quantitative analysis using a UV-Vis spectrophotometer at a wavelength of 276 nm revealed the average diclofenac sodium contents as follows: sample A = 17.911%, B = 20.691%, C = 21.016%, D = 20.902%, E = 23.350%, and F = 23.772%. These findings indicate that all analyzed jamu pegal linu preparations contained diclofenac sodium as a medicinal chemical adulterant (BKO). This study underscores the urgent need for stricter regulation, quality control, and consumer awareness to ensure the safety and authenticity of traditional herbal medicines in Indonesia.